Herodotus' Prologue and the Greek Poetic Tradition - Chiasson, Charles C. (Histos, 2012)
This article seeks to deepen our understanding of Herodotus’ relationship to Homer as reflected in the prologue, while shedding new light on his relationship to other poets and poetic traditions by focusing on: (1) the poetic device Herodotus uses to structure his opening discussion of the αἰτίη of the Greco-Persian wars (1.1–5), i.e., the priamel; and (2) his self-identification, at the end of his prologue, as a poetic sage whose understanding of historical development is informed by a fundamental principle of Greek gnomic wisdom, the transience of human prosperity.